Democratic Leadership and Work Environment Impact on Employee Performance: Dampak Gaya Kepemimpinan Demokratis, Lingkungan Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan: Studi Kuantitatif - Andrian Setyo Wibowo; Dewi Komala Sari (Academia Open, 2022)
This study aimed to investigate the influence of democratic leadership style, work environment, and work discipline on employee performance within the context of PT. Universal Prima Grafika in Sidoarjo. The research utilized a quantitative approach with hypothesis testing, and the sample consisted of 77 employees from the company. Multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classical assumption test were employed as analytical tools, utilizing SPSS version 18 for Windows. Primary data were collected through questionnaires employing a Likert scale, with validity and reliability testing conducted. The findings revealed significant effects of democratic leadership style, work environment, and work discipline on employee performance at PT. Universal Prima Grafika in Sidoarjo. These results contribute to our understanding of the factors influencing employee performance and have implications for organizational practices and managerial decision-making. Highlights: The study explores the impact of democratic leadership, work environment, and work discipline on employee performance. It employs a quantitative research approach with hypothesis testing and multiple linear regression analysis. The findings highlight the significant influence of democratic leadership, work environment, and work discipline on employee performance at PT. Universal Prima Grafika in Sidoarjo. Keywords: Democratic leadership, work environment, work discipline, employee performance, quantitative study.